Kajian Interaksi Inang â Patogen dan Peranan Jamur Mikoriza Arbuskular pada Penyakit Kuning Lada - , Suryanti, S.P., M.P. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Indonesia is the major producer of black pepper (Piper nigrum L.), however the pepper production has been decreasing in the last decade. Black pepper yellows is one of the most important disease on pepper causing the decrease of pepper production. Researchs of this disease has been done for a long time, however an effective and efficient methods for controlling the disease is still unknown. This research aimed to determine the major causal agent of yellows disease, hostpathogen interaction, and the role of arbuscular mycorrhiza fungi (AMF) on development of pepper yellows disease. Surveys were conducted at several locations in pepper plantations (West Kalimantan, Bangka, and Lampung) to measure the severity of yellows disease and to collect samples for pathogen isolation purposes. Laboratory and greenhouse research were carried out for the identification of major pathogens causing the disease, observing responses of host plants against pathogen infection, and examine the role of the AMF to the growth and development of yellows disease of pepper. The result showed that from the plants with yellows disease symptom in West Kalimantan could be isolated nematode Meloidogyne incognita and fungi Fusarium solani. Pepper inoculated with both pathogens, showed that yellows disease of pepper could be caused by F. solani or M. incognita. A higher severity of the disease occured when plants were inoculated with M. incognita followed by F. solani. The pepper inoculated with M. incognita followed by F. solani could increase the peroxidase activity and lignification on pepper root as the respons of the host against pathogen attack. The physiological response of pepper inoculated with F. solani and M. incognita was the decrease of chlorophyll content of leaves, and the increase of transpiration activity. From the pepper plantation could be isolated Funneliformis sp. which inhibited the development of disease by increasing the plant growth.